Populaarimusiikkia kulttuuriperinnön kierrevirrassa. Hymy-lehden organisoima Olavi Virran muistomerkkihanke (1975–1984) kulttuuriperintöprosessina - Peltomäki Anna (Suomen musiikkitieteellinen seura, 2022)
The last decade has witnessed a proliferation of academic literature on the expanding heritagization of popular music. Despite this international academic interest, the theoretical underpinnings of cultural heritage studies have been underused in the study of Finnish popular music cultures.
This article presents a case study of a popular music heritage process in Finland. It examines an early monument scheme honouring one of the most renowned Finnish singers of the 20th century, Olavi Virta (1915–1972). In the article, the monument project – initiated by the tabloid magazine Hymy (engl. smile) in 1975 and completed in 1984 – is retraced as a chain of events in which Olavi Virta’s memory and oeuvre were reinterpreted and repurposed as national popular music heritage. Newspaper and magazine articles covering the monument scheme are analysed through the conceptual framework of cultural heritage identity work: historisation, monumentalisation and participation.
The article argues that the interviews, memoires and retrospective texts that Hymy published on Virta constituted a historicizing practice that paved the way for the artist’s later monumentalisation. The abstract-constructivist realisation of the monument, critiqued by some as inconsistent with the scheme’s popular objective, is interpreted as a visual parallel to the rehabilitative rhetoric with which Hymy covered the scheme. However, the monument may also be conceived of as the magazine’s assimilation of the beloved artist’s memory at a time when Hymy was struggling to establish a new editorial line in a changing media landscape. While the sculpture’s standing as the first public monument to celebrate Finnish popular music is in question, the article maintains that the Virta monument may nonetheless be regarded as an important forerunner to the mounting public memorialisation of popular music in Finland.